STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA TRANSPORTASI - Muhammad Yusuf (Politeknik Penerbangan Indonesia Curug, 2019)
In its relation with the Human Resources aspect Development Agency of Human Resources Development of Transportation, has strategic role in supervising the human resources of transportation, include in it supervision on the personnel or human resources performers of the activities in the implementation and service in the area of transportation, whether managerially as well as operational technique. Education and training for Development of Human Resources of Transportation is very important because it will help the procurement and update of the knowledge and skills of the employees in accordance with the competency standard needed. Therefore it is expected the transportation service level to the public in the future will be higher. The purpose of this Paper writing is to obtain an educational design and training related to the Development Strategy of Transportation Human Resources, it is expected to be able to support the activity of Economic, Social, Culture, Security Defense and Politic through its role to what extent in the area of transportation needed in Indonesia as well as international market currently and in the future in accordance with the competency standard/ skills needed. The objective is to prepare a design in the form of framework and structure which are able to identify and to provide Education and Training about the Strategy of Human Resources Development of Transportation.